(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: the idiopathic nephrotic syndrome (INS) is the most common glomerulopathy in pediatrics. The purpose of this study is to estimate the INS incidence in pediatric public health patients and to describe their response to treatment and their evolutionary characteristics and complications. Methods: a descriptive study was carried out of a historical cohort of patients under 15 years of age with first time INS assisted in the Nephrological Clinic of the Pereira Rossell Hospital Center between 01/01/2009 - 12/31/2013, monitored until 12/31/ 2015, users of the State Health Services (ASSE). Their annual incidence was estimated according to data obtained from the National Data System Report (SINADI) of the Ministry of Public Health. We recorded age, sex, height, body mass index, response to initial treatment and evolution and followed them up >12 months. Results: we included 42 patients with a male / female ratio 2.2 / 1; the SNI annual incidence in the ASSE population was 3.05 / 100,000 children under 15 years of age. 34 were cortico-sensitive (CS) and 8 cortico-resistant (CR). The mean age of the first incident was 5 years in CS and 2 years 10 months in CR. The evolution was analyzed in the 33 patients monitored for a period of time >12 months, with a mean follow-up of 4 years ± 1 year 9 months; In these children, the frequency of CS was 78.7% (n = 26) and of RC 21.3% (n = 7). Within the CS, there were 10 (38.6%) cortico-dependents / frequent relapsers (DC), 8 had sporadic relapses and 8 did not relapse. Among the DCs, 5 received cyclophosphamide, in one patient prednisone was suspended at 3 months, in 2 of them the dose was lowered and the other 2 did not respond, one of them achieved sustained remission with cyclosporine. Of the 7 RCs, 4 had initial remission with cyclosporine, 1 partial remission and 2 were resistant; 3 received mycophenolate mofetil, 2 did not respond, and 1 had partial remission. The biopsy in all the RCs showed focal and segmental hyalinosis. The genetic study for NPHS2 and WT1 carried out on 4 patients was negative. At the end of follow-up, all CS patients were in remission, 16/26 without treatment. Among the RCs, 2 were in remission with cyclosporine, 4 maintained nephrotic proteinuria (one of them with a drop in glomerular filtration rate of 60 ml/min/1.73m2 sc), and another was on chronic dialysis. Serious infectious complications occurred in 5 CR and 2 CS patients. One CD and one CR patient developed chronic arterial hypertension. In CD and RC, a significant difference was observed in the Z score of the BMI and height between the beginning and the end of the follow-up. Conclusions: the calculated incidence includes only patients treated by the State Health Services in our country; it does not reflect the global incidence at national level, and it is comparable to that of other series. The evolution of CS and CR patients was also similar to those described. The growth of children exposed to long-term corticosteroid treatment was affected. For best results, these patients should be offered customized treatment according to current recommendations.